Psychometric evaluation of the SF-36 (v.2) questionnaire in a probability sample of Brazilian households: results of the survey Pesquisa Dimensões Sociais das Desigualdades (PDSD), Brazil, 2008 - Laguardia, Josué; Campos, Monica R; Travassos, Claudia M; Najar, Alberto L; Anjos, Luiz A; Vasconcellos, Miguel M (Health and quality of life outcomes, 2011)
Background In Brazil, despite the growing use of SF-36 in different research environments, most of the psychometric evaluation of the translated questionnaire was from studies with samples of patients. The purpose of this paper is to examine if the Brazilian version of SF-36 satisfies scaling assumptions, reliability and validity required for valid interpretation of the SF-36 summated ratings scales in the general population. Methods 12,423 individuals and their spouses living in 8,048 households were selected from a stratified sample of all permanent households along the country to be interviewed using the Brazilian SF-36 (version 2). Psychometric tests were performed to evaluate the scaling assumptions based on IQOLA methodology. Results Data quality was satisfactory with questionnaire completion rate of 100%. The ordering of the item means within scales clustered as hypothesized. All item-scale correlations exceeded the suggested criteria for reliability with success rate of 100% and low floor and ceiling effects. All scales reached the criteria for group comparison and factor analysis identified two principal components that jointly accounted for 67.5% of the total variance. Role emotional and vitality were strongly correlated with physical and mental components, respectively, while social functioning was moderately correlated with both components. Role physical and mental health scales were, respectively, the most valid measures of the physical and mental health component. In the comparisons between groups that differed by the presence or absence of depression, subjects who reported having the disease had lower mean scores in all scales and mental health scale discriminated best between the two groups. Among those healthy and with one, two or three and more chronic illness, the average scores were inverted related to the number of diseases. Body pain, general health and vitality were the most discriminating scales between healthy and diseased groups. Higher scores were associated with individuals of male sex, age below 40 years old and high schooling. Conclusions The Brazilian version of SF-36 performed well and the findings suggested that it is a reliable and valid measure of health related quality of life among the general population as well as a promising measure for research on health inequalities in Brazil.